Consequences of switching from prophylactic treatment to on‐demand treatment in late teens and early adults with severe haemophilia A: the TEEN/TWEN study. (11th June 2013) - Manco‐Johnson, M. J.; Sanders, J.; Ewing, N.; Rodriguez, N.; Tarantino, M.; Humphries, T.; ,
Summary: Although many people with haemophilia discontinue prophylaxis in their late teens or early adulthood, the consequences of this decision are largely not known. This 18‐month, observational, case‐controlled, multicentre study evaluated long‐term prophylaxis and the consequences of switching from prophylaxis to on‐demand treatment in late teens and young adults with severe haemophilia A. Participants with haemophilia (aged 14–29 years) on prophylaxis ≥60% of the time for the 5 years before study entry were enrolled into 1 of 2 prospective or 1 retrospective group. Group 1 was prophylaxis, group 2 had voluntarily discontinued prophylaxis ≤12 months before study entry and group 3 had voluntarily discontinued prophylaxis ≥13 months before study entry. Assessments included bleeding frequency (primary endpoint), Haemo‐QoL‐A health‐related quality of life (HRQoL) scores, Gilbert score, development of target joints, Haemophilia Activities List, Godin Leisure‐Time, treatment satisfaction and State‐Trait Anxiety Inventory (secondary and exploratory endpoints). Descriptive statistics were provided for all variables. Thirty‐eight participants (group 1, n  = 22; group 2, n  = 5; group 3, n  = 11; median age, 19.5 years) were enrolled. The median annualized number of bleeding events was 0, 4.8 and 24 in groups 1, 2 and 3 respectively. HRQoL was lower in participants who discontinued prophylaxis vs. those who remained on prophylaxis. Changes in the remaining secondary and exploratory variables were small, but were generally worse in participants who discontinued prophylaxis. Following a switch from prophylaxis to on‐demand therapy, the number of bleeding events increased and HRQoL worsened in late teens and young adults with severe haemophilia A.